Deixis in Judith McNaught’s Night Whispers Novel - Witri Afrilian; Diana Rozelin; Awliya Rahmi (Indonesian Journal of EFL and Linguistics, 2019)
This paper aims to examine the types of deixis, the meaning of deixis, and the position of deixis in novel entitled Night Whispers written by Judith McNaught. The authors applied theory of deixis from Levinson (1983) and theory of meaning by Chaer (2013). The analysis of this research uses distributional and referential identity method by Sudaryanto (1993). The results show that there are five types of deixis which is found in the novel with the most-found type is person deixis and the fewest-found type is social deixis. The meanings of the deixis are referred to the speaker herself which is named Sloan, Sloan’s friend named Sara, the time when Sloan uttered the utterance, the span when Sloan lived as police officer, Sloan’s father’s house, Apparition, the thought of Sloan of a group of girl, the thing Sloan wanted Paris to remember, and Sloan’s great-grandmother. The position of the deixis is as Noun, Pronoun, Adjective, and Adverb.